Establishing half saturation constant for nitrate in bulk water under anoxic conditions / Norjiha Abu Bakar - Abu Bakar, Norjiha (2002)
The sewer is an integral part of the urban wastewater system: the sewer, the wastewater treatment plant and the local receiving waters. The sewer is a reactor for microbial changes of the wastewater during transportation, affecting the quality of the wastewater and thereby the successive treatment processes or receiving water impacts during combined sewer overflows. This project presents the results of studies on anoxic processes, namely denitrification, under sewer condition. Experiments were conducted on 5 samples taken from two locations, namely, the Wastewater Treatment Plant at Section 23, Shah Alam and UiTM Packaged Sewage Treatment Plant at Jln Ilmu, UiTM Shah Alam. Tests were performed using batch reactors to measure denitrification rate under conditions of excess electron donor and limited electron acceptor. Concentrations of electron acceptors in samples i. e nitrate and nitrite were determined using Metrohm Ion Chromatograph 790 COM. Experiments conducted on wastewater sample have shown that the value of half saturation constant, KN03 were found to be in the range of 0.3 -1.2 gN03-N/m3.h.